2002
DOI: 10.1001/archopht.120.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Leopard-Spot Pattern of Yellowish Subretinal Deposits in Central Serous Chorioretinopathy

Abstract: To describe clinical and angiographic features of patients with central serous chorioretinopathy (CSC) who had yellowish subretinal deposits forming a reticulated leopard-spot pattern during fluorescein angiography. Methods: We conducted case studies using the clinical and photographic records of 5 patients. Results: All 5 patients were older men between the ages of 68 and 81 years who had been treated with corticosteroids and had bilateral CSC. Nine eyes of the 5 patients developed yellowish deposits in a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Figure is from Laud et al 79 Reprinted with permission from the Ophthalmic Communications Society, Inc. and Lippincott Williams & Wilkins. mulation of this material may explain previously reported findings of yellow material accumulating in the subretinal space in patients with CSC. 42,43 The small punctuate areas of hyperautofluorescence colocalize with the small white dots seen by ophthalmoscopy on the undersurface of the retina. The number of the dots varies in number, but there is not much variability in size of the dots.…”
Section: Cscmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure is from Laud et al 79 Reprinted with permission from the Ophthalmic Communications Society, Inc. and Lippincott Williams & Wilkins. mulation of this material may explain previously reported findings of yellow material accumulating in the subretinal space in patients with CSC. 42,43 The small punctuate areas of hyperautofluorescence colocalize with the small white dots seen by ophthalmoscopy on the undersurface of the retina. The number of the dots varies in number, but there is not much variability in size of the dots.…”
Section: Cscmentioning
confidence: 79%
“…2 In addition, several patients have been described who had focal central serous leaks and later developed yellowish accumulation of subretinal material mimicking that seen in AFVD and VMD2. 42,43 Although the basic defect in VMD is related to an abnormal Clchannel in the RPE and thus may differ from the underlying etiologic cause of CSC, the net result for VMD patients may be the presence of subretinal fluid and associated altered outer segment turnover as a consequence.…”
Section: Vmdmentioning
confidence: 99%
“…FFA has been used to reveal focal leakage sites in the RPE, and it has been suggested that this leakage causes the RPE or neurosensory retinal detachment [13,14]. In contrast, choroidal vascular hyperpermeability has been suggested as the primary cause of damage to the RPE in some reports, and this increased permeability has been demonstrated using indocyanine green angiography [15]. As a support for the choroidal hyperpermeability, the According to the Bonferroni correction, p < 0.017 was considered statistically significant CSCR central serous chorioretinopathy, GCC ganglion cell complex a Statistically significant difference between the acute CSCR and control groups b Statisticalyl significant difference between the chronic CSCR and control groups plasma levels of plasminogen activator inhibitor 1 concentrations were found to be significantly higher in patients with CSCR as compared with normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic CSC may be associated with persistent subretinal exudation, extensive RPE atrophy, cystoid macular degeneration, and choroidal neovascularization. These factors lead to a less favorable visual prognosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%